Performance of novel virtual parenchymal perfusion software visualizing embolized areas of transcatheter arterial chemoembolization for hepatocellular carcinoma. Issue 5 (11th August 2016) - Miyayama, Shiro; Yamashiro, Masashi; Nagai, Keiichi; Yokka, Akira; Yoshida, Miki; Sakuragawa, Naoko
Abstract : Aim: To evaluate the performance of novel virtual parenchymal perfusion (VPP) software in conventional transcatheter arterial chemoembolization (cTACE) for hepatocellular carcinoma. Methods: VPP was retrospectively applied to 43 hepatocellular carcinomas treated with cTACE. The virtual embolized area (VEA) was estimated after positioning a virtual injection point on images of non‐selective cone‐beam computed tomography during hepatic arteriography, at the same position in superselective cTACE. The real embolized area (REA) was defined as the area where iodized oil was retained on 1‐week computed tomography after cTACE. Three dimensions across the tumor (maximum [a] and minimum [b] in the axial and craniocaudal [c]) directions, and the volume of the VEA and REA were compared using linear regression analysis. It was also evaluated whether an adequate safety margin ≥5 mm could be predicted by VPP. Results: The mean lengths of a, b, and c of the VEA and REA were 54.6 ± 15.9 mm (range 24.9–91.0 mm) and 55.0 ± 15.7 mm (range 23.9–92.8 mm; r  = 0.9448, P  < 0.001), 35.4 ± 11.7 mm (range 16.1–66.0 mm) and 35.4 ± 13.2 mm (range 12.2–69.2 mm; r  = 0.9369, P  < 0.001), and 42.1 ± 11.6 mm (range 25.0–75.7 mm) and 42.9 ± 11.7 mm (range 25.7–78.7 mm; r  = 0.9092, P  < 0.001), respectively. The mean volume of the VEA and REA was 71.8 ± 44.8 mL and 75.5 ± 46.9 mL, respectively ( r  = 0.9913, P  < 0.0001). VPP showed no safety margins in seven tumors, including all three actually embolized without safety margins. Conclusion: The VEA estimated using VPP showed a good correlation with the REA of cTACE.